Value of 3D MRI and Vaginal Opacification for the Diagnosis of Vaginal Endometriosis - Bazot, Marc; Beldjord, Selma; Jarboui, Lamia; Ferrier, Clement; Bendifallah, Sofiane; Daraï, Emile (Frontiers in Surgery, 2020)
Objective: The aim of the study was to evaluate three-dimensional (3D) T2 MRI before and after vaginal opacification (VO) by gel (3DT2VO) and the additional value of 3DT1 with fat-suppression (3DT1FS) MRI in the diagnosis of vaginal endometriosis. Methods: During a study period of three years, 51 patients scheduled for surgical treatment of endometriosis underwent MRI one day before surgery. Three readers (novice, intermediate, expert) were asked to diagnose vaginal endometriosis independently and blindly using four different readings (i.e. 3DT2, 3DT2VO, 3DT2 with 3DT1FS, 3DT2VO with 3DT1FS). Vaginal endometriosis diagnosis was positive on observation of a thickening of vaginal walls on 3DT2 with or without high-signal-intensity spots on 3DT2 and/or 3DT1FS. The reference standard was surgery and histology. Descriptive analysis, Chi-square test, and ROC curves were used for statistical analysis. Results: For all readers, the combination of 3DT2 and 3DT1FS significantly improved the diagnosis of vaginal endometriosis compared with 3DT2 (p=0.002, p=0.02 and p=0.003). 3DT2VO significantly improved diagnosis for the intermediate reader (p=0.01). High-signal-intensity spots on 3DT1FS had a sensitivity of 50%-63.6%, specificity of 86.2%-96.6%, and high positive likelihood ratios (14.5-Inf). Conclusion: 3DT2 in association with 3DT1FS appears to be the best 3D MRI protocol for the diagnosis of vaginal endometriosis, whatever the level of experience of readers. The additional value of 3DT2VO is variable among the readers.